2020
DOI: 10.1111/sms.13625
|View full text |Cite
|
Sign up to set email alerts
|

Is aerobic exercise helpful in patients with migraine? A systematic review and meta‐analysis

Abstract: Purpose:To assess the effects of aerobic exercise (AE) on patients with migraine in terms of pain intensity, frequency and duration of migraine, and quality of life. Methods: A systematic review and meta-analysis of randomized controlled trials were conducted. Standardized mean differences (SMDs) and 95% confidence intervals (CIs) were calculated for relevant outcomes and were pooled in a meta-analysis using the random-effects model. Results: A total of 10 articles from 1950 to 2019 were included, involving 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 73 publications
(294 reference statements)
3
35
0
5
Order By: Relevance
“…In the current study, we found that physical activity was associated with reduced odds of primary headaches. In agreement with our findings, a review article revealed that aerobic exercise can alleviate the duration of migraine headaches and also somewhat decrease the incidence of these headaches [33]. In another similar study, a beneficial effect of exercise on primary headaches including migraine and tension-type headaches and also a decrease in the use of headache-related medications were reported [34].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, we found that physical activity was associated with reduced odds of primary headaches. In agreement with our findings, a review article revealed that aerobic exercise can alleviate the duration of migraine headaches and also somewhat decrease the incidence of these headaches [33]. In another similar study, a beneficial effect of exercise on primary headaches including migraine and tension-type headaches and also a decrease in the use of headache-related medications were reported [34].…”
Section: Discussionsupporting
confidence: 91%
“…For instance, multiple small intervention studies have shown that regular aerobic exercise produces effects similar to pharmacologic and behavioral therapies 6‐9 and when combined with pharmacotherapy may improve outcomes exceeding those from medication alone 10 . More recently, a meta‐analytic review supported the conclusion that aerobic exercise improves migraine symptoms and quality of life 11 . Similarly, prospective population studies have shown that physical inactivity predicts onset of headache, 12,13 and cross‐sectional population studies indicate that migraine prevalence and frequency are inversely associated with PA 13‐15 …”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, el ejercicio aeróbico ha mostrado ser una intervención segura y con moderada evidencia para mejorar su calidad de vida de estas personas (La Touche et al, 2020). Además, el ejercicio aeróbico ha mostrado tener efectos profilácticos similares a los de la medicación preventiva de la migraña como es el Topiramato, por lo que podría ser una opción clínica profiláctica a tener en cuenta durante la fase no sintomática del ciclo menstrual en esta población.…”
Section: Discussionunclassified